2019
DOI: 10.3390/ijms20143491
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dental Sealant Containing Dimethylaminohexadecyl Methacrylate Suppresses the Cariogenic Pathogenicity of Streptococcus mutans Biofilms

Abstract: Cariogenic oral biofilms are strongly linked to dental caries around dental sealants. Quaternary ammonium monomers copolymerized with dental resin systems have been increasingly explored for modulation of biofilm growth. Here, we investigated the effect of dimethylaminohexadecyl methacrylate (DMAHDM) on the cariogenic pathogenicity of Streptococcus mutans (S. mutans) biofilms. DMAHDM at 5 mass% was incorporated into a parental formulation containing 20 mass% nanoparticles of amorphous calcium phosphate (NACP).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…The present findings are in agreement with other studies to some degree since this is a first‐time investigation on coculture of S. mutans and C. albicans . For S. mutans biofilm formation, the substantial 3–4 log reduction for biofilm growth over DMAHDM confirms previous in vitro studies regarding the antimicrobial activity of DMAHDM with concentration variation from 3% to 5% (Ibrahim et al, 2019; Wang et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present findings are in agreement with other studies to some degree since this is a first‐time investigation on coculture of S. mutans and C. albicans . For S. mutans biofilm formation, the substantial 3–4 log reduction for biofilm growth over DMAHDM confirms previous in vitro studies regarding the antimicrobial activity of DMAHDM with concentration variation from 3% to 5% (Ibrahim et al, 2019; Wang et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…We have reported screened formulations that reach acceptable rates for physical and mechanical properties using DMAHDM and amorphous calcium phosphate nanoparticles (NACPs), respectively (Ibrahim et al, 2018). Furthermore, we have suggested a role of DMAHDM in the reduction of S. mutans virulence factors (Ibrahim et al, 2019). Concerning the incorporation of nanosized amorphous calcium phosphate, a high rate of calcium and phosphate ions release was observed over 2months, and the recharge of the ions and subsequent release were successfully reached with this biointeractive tooth sealing formulation (Al‐Dulaijan et al, 2018; Al‐Qarni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…QACs have been studied due to their high and broad antibacterial spectra, even at small concentrations [25][26][27]. In the case of TAT, it was suggested that the mechanism of antibacterial action is due to "contact killing" effect [6].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, DMAHDM was incorporated into resin-based materials and exhibited an excellent antimicrobial activity [ 25 , 26 , 27 ]. It has been reported that DMAHDM is a positively charged monomer with the ability to work through direct contact killing mechanisms by interacting with negatively charged bacterial cell membranes, causing bacterial cell disturbance and lysis [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…DMAHDM and NACP were incorporated into dental adhesives, pit and fissure sealants, and resin composites in previous studies. They presented strong antibacterial outcomes with a high level of Ca 2+ and PO 4 3− ion release [ 20 , 25 , 30 , 31 ]. Consequently, the incorporation of DMAHDM and NACP into a resin-based material could help to prevent dental caries through DMAHDM contact inhibition action and tooth remineralization through the release of Ca 2+ and PO 4 3− ions into the tooth-restoration interface [ 25 , 32 ].…”
Section: Introductionmentioning
confidence: 99%